Disulfiram Improves the Anti-PD-1 Therapy Efficacy by Regulating PD-L1 Expression via Epigenetically Reactivation of IRF7 in Triple Negative Breast Cancer - Zheng, Xin; Liu, Zijian; Mi, Mi; Wen, Qiuyue; Wu, Gang; Zhang, Liling (Frontiers in Oncology, 2021)
Immune checkpoint blockade (ICB), particularly programmed death 1 (PD-1) and its ligand (PD-L1), has shown considerable clinical benefits in patients with various cancers. Many studies show that PD-L1 expression may be biomarkers to help select responders for anti-PD-1 treatment. Therefore, it is necessary to elucidate the molecular mechanisms that control PD-L1 expression. As a potential chemosensitizer and anticancer drug, disulfiram (DSF) kills tumor cells via regulating multiple signaling pathways and transcription factors. However, its effect on tumor immune microenvironment (TIME) remains unclear. Here, we showed that DSF increased PD-L1 expression in triple negative breast cancer (TNBC) cells. Through bioinformatics analysis, we found that DNMT1 was highly expressed in TNBC tissue and PD-L1 was negatively correlated with IRF7 expression. DSF reduced DNMT1 expression and activity, and hypomethylated IRF7 promoter region resulting in upregulation of IRF7. Furthermore, we found DSF enhanced PD-L1 expression via DNMT1-mediated IRF7 hypomethylation. In vivo experiments, DSF significantly improved the response to anti-PD-1 antibody (Ab) in 4T1 breast cancer mouse model. Immunohistochemistry staining showed that granzyme B+ and CD8+ T cells in the tumor tissues were significantly increased in the combination group. By analyzing the results of the tumor tissue RNA sequencing, four immune associated pathways were significantly enriched in the DSF joint anti-PD-1 Ab group. In conclusion, we found that DSF could up-regulate PD-L1 in TNBC cells and elucidated its mechanism. Our findings revealed that the combination of DSF and anti-PD-1 Ab could activate TIME to show much better antitumor efficacy than monotherapy.